Adopsi Komunikasi Persuasi Ibu Muda dalam Pengembangan Bisnis Multi-Level Marketing (MLM): Adoption of Persuasion Communication of Young Mothers in Multi-Level Marketing (MLM) Business Development - Vina Mahdalena; Lusia Handayani; Uljanatunnisa Uljanatunnisa (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Business competition has given birth to a network marketing system or what is commonly referred to as Network Marketing. The utilization used in Network Marketing, or what we currently know as MLM (Multi-Level Marketing), uses a network system where interpersonal communication is required both between MLM members and communication between members, customers, and prospective consultants. The interpersonal communication of consultants determines MLM business. How do they apply persuasive communication to persuade consumers or other consultants to join their network? This research uses a case study method. The results illustrate three important things young mothers do when running an MLM business to build the household economy. First, a trustworthy communicator will build credibility. Second, I need to understand how to convey messages in the MLM trading system; third, I need to choose communication channels that follow the objectives.